PENGEMBANGAN ALAT PERAGA EDUKATIF DI TK FALAH ALMUNTAZIR DUSUN III TANJUNG GUSTA SUMATERA UTARA - Marsella, Emma; Tumanggor, Winny R.E.; Harahap, Nurhayati (Smart Education, 2024)
Abstract: The general problems in this Community Service are first: the lack of educational teaching aids made by PAUD teachers in the classroom learning process, second: the lack of ideas for PAUD teachers in developing educational teaching aids in the classroom learning process so that teachers always use the same media in learning process in the third class: there is a lot of waste from used goods that can be utilized in the learning process so that the teacher automatically becomes an agent of change in reducing waste from used goods because it has been utilized optimally in making media in learning. Making educational teaching aids is not as easy as imagined because teachers have to consider aspects starting from planning the selection of learning media which includes (1) Learning planning in Kindergarten/PAUD (2) Learning targets, namely children (3) Whether the media's readability level meets technical requirements. such as clarity, size, and color arrangement. (4) Suitability to the situation and conditions of the place, such as land area, institutional environment, and community resources around the institution and fourth: Objectivity must avoid choosing media based solely on personal pleasure. Keywords: Educational Teaching Aids, PAUD, Development Abstrak: Permasalahan umum dalam Pengabdian Masyarakat ini adalah pertama: masih minimnya pembuatan Alat Peraga Edukatif oleh guru PAUD dalam proses pembelajaran di kelas , kedua : kurang nya ide bagi guru PAUD dalam mengembangkan Alat Peraga Edukatif dalam proses pembelajaran di kelas sehingga guru selalu nenggunakan media yang sama dalam proses pembelajaran di kelas ketiga: banyak nya llimbah barang bekas yang bisa di manfaatakan dalam proses pembelajaran sehingga dengan sendirinya maka guru menjadi agen of Change dalam pengurangan limbah barang bekas karena telah dimanfaatkan dengan maksimal dalam pembuatan media di dalam pembelajaran. Dalam Pembuatan Alat Peraga Edukatif memang tidak semudah yang dibayangkan karena guru harus mempertimbangkan aspek mulai dari perencanaan pemilihan media pembelajaran yang meliputi (1) Perencanaan pembelajaran di TK/ PAUD (2) Sasaran belajar yaitu anak (3) Tingkat keterbacaan media apakah sudah memenuhi syarat teknis seperti kejelasan, ukuran, dan pengaturan warna.(4) Kesesuaian dengan situasi dan kondisi tempat , seperti luas lahan, lingkungan lembaga, dan sumber daya masyarakat di sekitar lembaga dan keempat: Objektivitas harus terhindar dari pemilihan media yang didasari oleh kesenangan pribadi-pribadi semata. Kata kunci: Alat Peraga Edukatif, PAUD, Pengembangan